2020
DOI: 10.14740/jcs401
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Gaps in Online Resources for Cirrhotic Patients

Abstract: Background:The average readability level in the USA is a sixth grade level and for patients with chronic disease it is lower. Cirrhosis is a prevalent chronic disease that requires complex knowledge and instructions to manage. No research has been done about the understandability of online educational content for cirrhotic patients. Patients can find online materials curated by both general health platforms and high-volume liver transplant centers, and thus these materials were analyzed.Methods: After determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…(15) Another study showed that online resources available to patients through health platforms and hepatology centers were lengthy and complex, highlighting the limited availability of easyto-understand information for this patient population. (16) ChatGPT (Generative Pre-trained Transformer) is a natural language processing (NLP) model developed by OpenAI. (17) It generates human-like text for use in chatbot conversations.…”
Section: Introductionmentioning
confidence: 99%
“…(15) Another study showed that online resources available to patients through health platforms and hepatology centers were lengthy and complex, highlighting the limited availability of easyto-understand information for this patient population. (16) ChatGPT (Generative Pre-trained Transformer) is a natural language processing (NLP) model developed by OpenAI. (17) It generates human-like text for use in chatbot conversations.…”
Section: Introductionmentioning
confidence: 99%
“…15 Another study showed that online resources available to patients through health platforms and hepatology centers were lengthy and complex, highlighting the limited availability of easy-to-understand information for this patient population. 16 ChatGPT (Generative Pre-trained Transformer) is a natural language processing (NLP) model developed by OpenAI. 17 It generates human-like text for use in chatbot conversations.…”
Section: Introductionmentioning
confidence: 99%
“…15 Another study showed that online resources available to patients through health platforms and hepatology centers were lengthy and complex, highlighting the limited availability of easy-to-understand information for this patient population. 16…”
Section: Introductionmentioning
confidence: 99%
“…37,38 However, informed decision-making can be difficult to achieve for patients who have low health literacy. [78][79][80][81][82] Furthermore, improved knowledge does not always translate into better decision-making and improved access to SOT or LDKT. A randomized study involving 499 patients with ESKD presenting for KT evaluation assessed the efficacy of a 25-min video (information about donor evaluation, surgery, and life after donation) followed by a 15-min meeting with a transplant educator compared with standard pretransplant education (90-min slide presentation without a transplant educator session).…”
Section: Transplant-related Knowledge and Treatment Decisionsmentioning
confidence: 99%